8.3k views
1 vote
3/4 + (1/3 • 1/6) - ( - 1/2) = ?

A) 3 1/4
B) 2 1/4
C) 1 3/4
D) 3/4

3/4 + (1/3 • 1/6) - ( - 1/2) = ? A) 3 1/4 B) 2 1/4 C) 1 3/4 D) 3/4-example-1

2 Answers

2 votes

9514 1404 393

Answer:

A) 3 1/4

Explanation:

Your calculator can help with this.

__

3/4 + ((1/3)/(1/6)) -(-1/2)

= 3/4 + ((2/6)/(1/6)) + 2/4

= 5/4 + 2/1

= 3 1/4

User Namanyay Goel
by
5.0k points
4 votes

Q) 3/4 + {(1/3) ÷ (1/6)} - ( - 1/2) = ?

→ 3/4 + {(1/3) ÷ (1/6)} - ( - 1/2)

→ 3/4 + {(1/3) × (6/1)} - ( - 1/2)

→ 3/4 + 6/3 - ( - 1/2)

→ {(3/4) + (6/3)} + 1/2

→ 11/4 + 1/2

→ (11 + 2)/4 = 13/4

→ 3 1/4

Hence, option (A) is the answer.

User Alexander Klauer
by
4.7k points